Bottom-up design process of agri-environmental measures at a landscape scale: Evidence from case studies on biodiversity conservation and water protection. (November 2017) - Toderi, Marco; Francioni, Matteo; Seddaiu, Giovanna; Roggero, Pier Paolo; Trozzo, Laura; D'Ottavio, Paride
Highlights: Agri-environmental measures (AEMs) with landscape goals are analysed. A legal arrangement for the inclusion of the landscape approach in AEMs is analysed. Inclusion of local knowledge leads to site-specific and/or landscape scale AEMs. A shift in stakeholder roles is needed for natural resources co-management. A framework for site-specific and/or landscape AEM design processes is proposed. Abstract: An Agri-environmental measure (AEM) is a payment to farmers to reduce environmental risks or to preserve cultivated landscapes. The single farm scale that is the basis for the AEM has often inhibited the achievement of the environmental goals since many biophysical processes (e.g. soil erosion, water pollution, biodiversity losses) occur at landscape scale. This creates a spatial scale mismatch between the implementation scale of the measures and the ecological processes controlling the target agri-environmental issues. In this paper, we propose how to address this spatial scale mismatch by analysing nine case studies of AEMs implementation at landscape scale concerning biodiversity conservation and water protection. The analysis highlights that the inclusion of the landscape scale in AEMs depends on the level of the involvement of the local stakeholders (SH) in the building process. When the authorities created the space for the SHs to participate in the defining process of AEMs, the inclusion of local knowledge led to the emergence of new landscape and site-specific AEMs which were not previously considered by the autorities. On the contrary, when the SHs were only allowed to choose among the AEMs predefined by the authorities, many site specificity and acceptance issues arose. The creation of space in Rural Development Programmes for collaborative, bottom-up and landscape scale AEMs and the overcoming of institutional constraints in the design of specific actions are the key ingredients for the successful adoption of measures and for enhancing their effectiveness. In this paper, we explore in depth what made these stories successful and provide a framework for the implementation of site-specific and landscape AEMs.